2015
DOI: 10.1039/c5dt00400d
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral substitution as a tool for tuning electron-accepting properties of phthalocyanine analogs in intramolecular charge transfer

Abstract: The intramolecular charge transfer (ICT), which is a pathway for excited state relaxation, was studied on the newly synthesized zinc(ii) complexes of tetrapyrazinoporphyrazines bearing one fixed donor (i.e., a dialkylamino substituent). The rest of the peripheral substituents on the core was designed with respect to their different electronic effects (OBu, neopentyl, StBu, COOBu). The photophysical (singlet oxygen and fluorescence quantum yields) and electrochemical (reduction potentials) properties were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…[21] These resultsa re in good agreement with our previouss tudy on the structural aspects that influence ICT. [21,23] Specifically, the presence of two nitrogen donors on the TPyzPz core guarantees nearly complete quenching of the excited states, and therefore, the OFF state of the sensors is almost non-fluorescent.…”
Section: Photophysical Properties Of the Sensors In The Off Statementioning
confidence: 99%
“…[21] These resultsa re in good agreement with our previouss tudy on the structural aspects that influence ICT. [21,23] Specifically, the presence of two nitrogen donors on the TPyzPz core guarantees nearly complete quenching of the excited states, and therefore, the OFF state of the sensors is almost non-fluorescent.…”
Section: Photophysical Properties Of the Sensors In The Off Statementioning
confidence: 99%
“…The efficient lifetimes of 1a and 2a are comparable in the same solvent and slightly shorter in DMF (4.24–4.57 ns) than in MeOH (5.56–5.97 ns). The time-resolved data and emission range imply that for dyes 1a and 2a , the ICT character is lessened, and the fluorescence may originate from π→π * excited state because ICT is a competitive relaxation process of the singlet excited state and typically reduces the fluorescence [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…[30] [b] in M À1 .cm À1 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 represents a continuous, non-destructive and real-time method. [13,20,38] In this approach, bioluminescence is directly correlated with viable cells, because only the active cells are able to produce light. [39] However, the light emission of biofilms tends to be lower than in planktonic cells, due to nutrient starvation and oxygen availability, i. e., a reduction in the biofilm light emission may not always correspond to an irreversible inactivation of the cells.…”
Section: Photodynamic Inactivation Of Planktonic E Coli and Cellularmentioning
confidence: 99%
“…It has been demonstrated that insertion of amine groups is also a good strategy for quaternization and optimization of Pc photosensitizing abilities [32–34]. The presence of amine groups can induce a red shift effect in the Q‐band of Pc, which could be a major advantage when applying PDI for clinical purposes ,. The cellular localization and preferential binding sites are strongly influenced by the molecular structure as well as the nature, number and distribution of charges on the PS.…”
Section: Introductionmentioning
confidence: 99%